Quranic guidance and its impact on enhancing the mental health of youth - selected models (Journal of the College of Basic Education, 2025)
The study dealt with ethics from a Quranic perspective, as ethics are necessary for the individual and society, and Islam emphasized their importance and the good effect they have on society in general, mentioning the most important types of them, necessary and acquired, explaining the methods of acquiring them in Islam. Then the study dealt with the reasons for the decline of ethics in Islamic society from cultural invasion, globalization, and the efforts of some countries to destroy Islamic ethics.